2015
DOI: 10.1016/j.jcmg.2015.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Native T 1 Mapping by 3-T CMR Imaging for Characterization of Chronic Myocardial Infarctions

Abstract: Chronic MIs in STEMI and NSTEMI patients can be reliably characterized using threshold-based detection on native T1 maps at 3-T. Visual detection of chronic MIs on native T1 maps in both patient populations has high specificity, but modest sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 34 publications
3
66
0
Order By: Relevance
“…38) These findings were correlated with results from endomyocardial biopsy in other studies. [39][40][41] Approaching a frequent dilemma in clinical practice, a recent study showed that native T1 clearly discriminates between HCM and hypertensive heart disease (HHD), with T1 values being significantly increased at the former.…”
Section: )supporting
confidence: 78%
“…38) These findings were correlated with results from endomyocardial biopsy in other studies. [39][40][41] Approaching a frequent dilemma in clinical practice, a recent study showed that native T1 clearly discriminates between HCM and hypertensive heart disease (HHD), with T1 values being significantly increased at the former.…”
Section: )supporting
confidence: 78%
“…117 T1-mapping indices are also able to Cardiac event (hospitalizations for cardiovascular reasons, cardiac deaths), multivariate analyses were performed for imaging parameters separately; in the combined multivariate analysis clinical and imaging parameters, age, atrial fibrillation, previous CABG, and RV size were identified as the independent predictors; detect myocardial replacement scar, 40,118 although the exact delineation of the scar area remains challenging because of the presently insufficient spatial resolution and low signal to noise ratio. Finally, native T1 can reflect an increase in myocardial blood volume at rest as a compensatory mechanism for an increased resistance to blood flow because of a stenotic coronary artery, allowing recognition of ischemic areas.…”
Section: T1 Mapping In Acute Myocardial Ischemia and Infarctionmentioning
confidence: 99%
“…Recent studies have also investigated whether native T1-mapping (pre-contrast) can assess MI size. Kali and colleagues 44 showed that chronic MI (median of 13.6 years post-MI) could be detected using native T1-mapping at 3T in a small cohort of 25 patients. Liu and colleaguesl 45 showed that native T1-mapping at 3T could also identify acute MI size.…”
Section: Recent Advances In the Role Of Cmr In Reperfused Stemi Patientsmentioning
confidence: 99%